2000
DOI: 10.1111/j.1745-9125.2000.tb00883.x
|View full text |Cite
|
Sign up to set email alerts
|

A Cross‐cultural Examination of the Link Between Corporal Punishment and Adolescent Antisocial Behavior*

Abstract: Several studies with older children have reported a positive relationship between parental use of corporal punishment and child conduct problems. This has lead some social scientists to conclude that physical discipline fosters antisocial behavior. In an attempt to avoid the methodological dificulties that have plagued past research on this issue, the present study used a proportional measure of corporal punishment, controlled for earlier behavior problems and other dimensions of parenting, and tested for inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
83
1
7

Year Published

2003
2003
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 117 publications
(97 citation statements)
references
References 45 publications
6
83
1
7
Order By: Relevance
“…Among a sample of Taiwanese and White American parents, the Taiwanese scored significantly lower on monitoring than the White American parents (Simons et al, 2000). Additionally, the interaction between parental monitoring and corporal punishment was not significant for the White American boys but was significant for the Taiwanese boys.…”
Section: Ethnicity and Parentingmentioning
confidence: 93%
See 1 more Smart Citation
“…Among a sample of Taiwanese and White American parents, the Taiwanese scored significantly lower on monitoring than the White American parents (Simons et al, 2000). Additionally, the interaction between parental monitoring and corporal punishment was not significant for the White American boys but was significant for the Taiwanese boys.…”
Section: Ethnicity and Parentingmentioning
confidence: 93%
“…Research suggests that ethnicity plays a role in parental monitoring; however, only a few studies could be identified, and results appear inconsistent (Shakib et al, 2003;Shumow & Lowmax, 2002;Simons, Wu, Lin, Gordon, & Conger, 2000).…”
Section: Ethnicity and Parentingmentioning
confidence: 99%
“…Para Widon (1997) O abuso físico é utilizado pelos pais para controlar os filhos, por meio de chutes, pontapés, socos e mordidas que machucam e causam dor; enfim, são punições físicas de vários tipos e intensidades com a utilização ou não de objetos para esse fim (GOMIDE, 2003;CARVALHO;. Essa prática inadequada apresenta uma correlação positiva entre o uso de punição física e o desenvolvimento de crianças apáticas, medrosas e antissociais (SIMONS et al, 2000;GOMIDE, 2003, PACHECO;HUTZ, 2009). Segundo Pettit et al (2001), mães que fazem uso da disciplina punitiva e severa desde a infância dos filhos são mais inclinadas a serem manipuladoras e intrusivas nos anos iniciais da adolescência, o que poderá prejudicar o desenvolvimento da autonomia nos filhos.…”
Section: ϯϯunclassified
“…Quando a ϯϳ exigência para obedecer é muito grande, o provável resultado no comportamento dos filhos é a hostilidade à obediência, resistência e comportamentos externalizantes (PATTERSON; REID; DISHION, 2002). O uso de formas severas de punição corporal pelos pais, em detrimento das práticas envolventes e carinhosas pode ensiná-las que a agressão e a coerção são maneiras legítimas de solucionar problemas, e assim, ao invés de eliminar o comportamento de punir, esse acaba se ampliando (SIMONS et al, 2000).…”
Section: ϯϯunclassified
See 1 more Smart Citation